2019
DOI: 10.1113/ep087216
|View full text |Cite
|
Sign up to set email alerts
|

Reduced insulin sensitivity in young, normoglycaemic subjects alters microvascular tissue oxygenation during postocclusive reactive hyperaemia

Abstract: New Findings What is the central question of the study?Are measures of reduced insulin sensitivity in young, normoglycaemic subjects correlated with near‐infrared spectroscopy‐derived microvascular responsiveness [tissue oxygen saturation reperfusion rate (STO2 upslope)] during postocclusive reactive hyperaemia? What is the main finding and its importance?A sevenfold range of hepatic insulin sensitivity is significantly correlated (r = 0.44, P = 0.02) with STO2 upslope after transient tissue ischaemia. Near‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
(50 reference statements)
1
16
0
Order By: Relevance
“…Muscle O 2 resaturation rate parameters (StO 2slope _ 10s , StO 2slope _ 30s , and StO 2slope _ until_base ) are largely adopted to assess reactive hyperemia in hypertensive individuals, 4 gestational diabetic women, 14 and older adults at risk for CVD disease, 7 , 10 , 17 among other clinical groups. 13 , 18 Our findings demonstrated that only StO 2slope _ 10s was significantly slower in older adults with CVD risk factors compared to healthy older adults and to healthy young individuals, suggesting that StO 2slope_10s may be a more sensitive NIRS parameter for assessing reactive hyperemia. The StO 2slope _ 10s has typically been adopted to assess O 2 resaturation rate, since previous studies have reported that this parameter is correlated with reactive hyperemia measured in the brachial artery 20 and with FMD response.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Muscle O 2 resaturation rate parameters (StO 2slope _ 10s , StO 2slope _ 30s , and StO 2slope _ until_base ) are largely adopted to assess reactive hyperemia in hypertensive individuals, 4 gestational diabetic women, 14 and older adults at risk for CVD disease, 7 , 10 , 17 among other clinical groups. 13 , 18 Our findings demonstrated that only StO 2slope _ 10s was significantly slower in older adults with CVD risk factors compared to healthy older adults and to healthy young individuals, suggesting that StO 2slope_10s may be a more sensitive NIRS parameter for assessing reactive hyperemia. The StO 2slope _ 10s has typically been adopted to assess O 2 resaturation rate, since previous studies have reported that this parameter is correlated with reactive hyperemia measured in the brachial artery 20 and with FMD response.…”
Section: Discussionmentioning
confidence: 63%
“… 8 - 10 The sudden increase in the StO 2 signal during reperfusion enables various StO 2 parameters to be calculated, which, in general, are interpreted as measures of microvascular function. 3 The majority of StO 2 parameters adopted in previous studies include reperfusion rate (i.e., upslope of the StO 2 signal during the initial 10 s and 30 s, and until the StO 2 signal reaches baseline values), 11 - 13 magnitude of reperfusion (i.e., total area under the curve [AUC] of StO 2 and the difference between the lowest and highest StO 2 value), 4 , 13 - 17 and others (e.g., time to StO 2 baseline, time to StO 2 maximum, and AUC above the baseline). 13 , 15 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…Building on this observation, using the same NIRS‐based reactive hyperaemia approach described above, Townsend, Deysher, Wu, and Barstow (2019) showed that although tissue reperfusion after arterial cuff occlusion was positively related to whole‐body insulin sensitivity (a precursor of cardiovascular disease), it was also negatively correlated with absolute tissue desaturation, and that the skeletal muscle metabolic rate (i.e. the change in tissue saturation throughout the cuff occlusion period) was positively related to whole‐body insulin sensitivity.…”
Section: Introductionmentioning
confidence: 97%
“…In order to simultaneously assess these responses, we combined NIRS-derived assessments of forearm muscle function and brachial artery FMD tests performed in obese and lean participants before and subsequent to an oral glucose tolerance test. [17][18][19][20][21] 2 | ME THODS…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this study aimed to evaluate whether mild obesity‐specific differences in forearm microvascular and brachial artery adjustments occurred in response to a load in glucose. In order to simultaneously assess these responses, we combined NIRS–derived assessments of forearm muscle function and brachial artery FMD tests performed in obese and lean participants before and subsequent to an oral glucose tolerance test 17–21 …”
Section: Introductionmentioning
confidence: 99%